VARIASI MORFOLOGI DAEMONOROPS FISSA KOMPLEKS DI MALESIA BARAT - Dwi Putri Ramadhani; Tatik Chikmawati; Himmah Rustiami (Floribunda, 2014)
Daemonorops fissa complex study in West Malesia has been done, based on 21 morphological characters of 355 herbarium specimen. D. fissa complex in West Malesia has unique characters such as peduncle erect to ± 2 cm, fruit globose, leaves alternate, length of involucrum 1 cm and endosperm ruminate. D. fissa complex in West Malesia consist of eight known species, namely D. angustifolia (Griff.) Mart., D. calicarpa (Griff.) Mart., D. fissa Blume, D. grandis (Griff.) Mart., D. lewisiana (Griff.) Mart., D. melanochaetes Blume, D. monticola (Grift) Mart., and D. stenophylla Becc. Three species are proposed as new synonym, D. binnendijkii Becc. and D. trichroa Miq. are synonim to D. angustifolia, whereas D. palembanica Blume as a synonim to D. melanochaetes.